A gentlewoman's guide to murder [large type] - Hamilton, Victoria, 1957- (Hamilton, Victoria, 1957- Gentlewoman's guide to murder, 2023)
"Scandal and slayings among Regency London's elite . . . Refusing to stand by while the wealthy men of London prey on their powerless scullery maids and other young women, Miss Emmeline St. Germaine has made it her mission to rescue the victims and threaten the men at dagger-point to cease their depravities. But mere hours after she pays just such a visit to a prominent knight, he's found murdered and all of London is aghast. Did the man-or woman-who murdered the knight know of her visit? Facing scandal and the ruination of her family, Emmeline must solve the crime before she and her work are exposed. But there are powerful forces at work to silence her-or worse, lead her to the hangman's noose for a crime she did not commit" --